Spectrally selective and adaptive surfaces for protection against radiative heating: ITO and VO2. (9th October 2012) - Försth, Michael; Zhao, Shuxi; Roos, Arne
SUMMARY Two surface materials for reducing absorptivity of heat radiation from fires have been investigated. The first is VO2, which is a thermochromic material. When the temperature of a VO2 surface increases over a certain temperature, it switches, ideally, from infrared (IR)‐absorbing to IR‐reflecting. VO2 window coatings are still on a research level, yet to be commercialized. In this study, VO2 powder available on the market was investigated. The thermochromic effect could be identified but was not large enough to significantly improve the fire properties of treated surfaces. Some thoughts concerning how to improve the performance of VO2 are discussed. The second investigated material is indium tin oxide (ITO), which is a so called low‐e coating, which means that it has low emissivity and absorptivity in the IR part of the spectrum. ITO is spectrally selective in the sense that it transmits visible light while reflecting a large fraction of the IR radiation, which is a rare property for surfaces in general but a typical property of thin electrically conducting non‐metallic films. It is shown that the application of ITO to poly(methyl methacrylate) (PMMA) significantly improves its fire properties. ITO coating is a mature technology already in widespread use today in the electronics industry. Copyright © 2012 John Wiley & Sons, Ltd.